Genetic variations and microbiome of the poultry red mite Dermanyssus gallinae - Nishide, Yudai; Sugimoto, Takafumi N.; Watanabe, Kenji; Egami, Hiroshi; Kageyama, Daisuke (Frontiers in Microbiology, 2022)
The poultry red mite Dermanyssus gallinae poses a significant threat to the health of hens and poultry production. A comprehensive understanding of D. gallinae is necessary to develop sustainable and efficacious control methods. Here we examined 144 D. gallinae collected from 18 poultry farms throughout the Japanese Archipelago for their genetic variations based on mitochondrial cytochrome c oxidase subunit I (COI) sequences, and microbiome variations based on amplicon sequencing of the 16S ribosomal RNA gene. According to COI sequencing, the Japanese samples were categorized into three haplogroups, which did not reflect the geographical distribution. Microbiome analyses found that the major bacteria associated with D. gallinae were Bartonella, Cardinium, Wolbachia, and Tsukamurella, with Bartonella being most predominant. Among 144 individual mites, all possessed one of the two major types of Bartonella (Bartonella sp. A), while 140 mites possessed the other type (Bartonella sp. B). The presence of the two strains of Bartonella was also confirmed by a single copy gene, rpoB. The presence of Bartonella in laid eggs suggested transovarial vertical transmission. Given that obligate blood-feeding arthropods generally require a supply of B vitamins from symbiotic bacteria, Bartonella may play an important role in mite survival. Rickettsiella, a major symbiont in European D. gallinae populations, and suggested to be an important symbiont by genomic data, was rarely found in Japanese populations. Cardinium detected from D. gallinae fell into a major clade found widely in arthropods, whereas Wolbachia detected in Japanese D. gallinae appear to be a new lineage, located at the base of Wolbachia phylogeny. Of the mitochondrial phylogeny, infection patterns of Cardinium and Wolbachia were strongly correlated, possibly suggesting one or both of the symbionts induce reproductive manipulations and increase spread in the host populations.